Peran Eksopolisakarida Azotobacter dan Bahan Organik untuk Meningkatkan Nodulasi dan Biomassa Kedelai pada Dua Ordo Tanah - Hindersah, Reginawanti; Rostini, Neni; Kalay, Agustinus Marthin; Harsono, dan Arief (Indonesia Society of Agronomy (PERAGI) and Department of Agronomy and Horticulture, Faculty of Agriculture, IPB University, Bogor, Indonesia, 2019)
Exopolysaccharide (EPS) produced by nitrogen-fixing bacteria Azotobacter protect nitrogenase from oxygen. In legume,EPS plays a role in the immobilization of rhizobia to the roots. The objective of this experiment was to study the effect of EPSAzotobacter and organic matter on increasing number of nodules and biomass of soybeans grown in Inceptisols and Ultisols;as well as nitrogen-fixing bacteria population in soybean rhizosphere. The experiment was set up in a completely randomizedblock design with five replications to test combined treatments of two doses of crude EPS and organic matter. Nodule number,shoot dry weight and nitrogen uptake, as well as Azotobacter and Rhizobium population in soybean grown in Inceptisolsfollowing crude EPS and compost application, were higher than those grown in Ultisols. The application of EPS and compostIn Ultisols did not affect the number of nodule and other traits, but in Inceptisols, adding 6.25 g of compost and 20 mL of EPSto each plant increased the number of nodules and shoot weight at 42 days after planting. However, the highest N uptake wasdemonstrated by soybean received 10 mL and 20 mL EPS along with 12.5 g compost.